Predictors of mortality in acute heart failure: interaction between diabetes and impaired left ventricular ejection fraction. (5th June 2014) - Go, Yun Yun; Allen, John Carson; Chia, Shaw Yang; Sim, Ling Ling; Jaufeerally, Fazlur Rehman; Yap, Jonathan; Ching, Chi Keong; Sim, David; Kwok, Bernard; Liew, Reginald
<x xml:space="preserve">Abstract</x> Aim The aim of this study was to test the hypothesis that diabetes modifies the risk of mortality in acute heart failure patients, especially in patients with impaired LVEF, and that impaired LVEF in turn modifies the risk of mortality in diabetic patients. Methods and results We studied 2121 patients with acute heart failure admitted at two centres in Singapore from 1 January 2008 to 31 December 2009. The date of the last follow‐up was 31 December 2011, with a median follow‐up time (interquartile range) of 914 (442–1190) days. Cox regression was used to estimate hazard ratios for all‐cause mortality in patients with LVEF ≥50%, LVEF 30–49%, and LVEF <30% relative to diabetic status. Impaired LVEF (<50%) in the presence of diabetes substantially increased the risk of mortality compared with non‐diabetics with LVEF <50%. The adjusted hazard ratio (aHR) and 95% confidence interval (CI) for diabetic patients with an LVEF of 30–49% (1.46, 95% 1.18–1.81) was not statistically different from the aHR in non‐diabetic patients with severely impaired LVEF of <30% (1.38, 95% CI 1.09–1.75) (P = 0.644). The deleterious effects of diabetes seemed to be confined to acute heart failure patients with impaired LVEF, as the mortality rate in patients with LVEF >50% was not increased. Other clinical predictors of mortality were ageing, prior myocardial infarction, systolic blood pressure >140 mmHg, creatinine ≥250 µmol/L, haemoglobin <9.0 g/dL, and prior stroke/transient ischaemic attack. Conclusion The interaction of diabetes and impaired LVEF in acute heart failure patients significantly amplifies the deleterious effects of each as distinct disease entities.